Postoperative Long-Term Outcomes and Independent Risk Factors of Non-Small-Cell Lung Cancer Patients With Propofol versus Sevoflurane Anesthesia: A Retrospective Cohort Study - Gao, Zhenglian; Xu, Jian; Coburn, Mark; Ma, Daqing; Wang, Kun (Frontiers in Pharmacology, 2022)
Background: Existing studies have shown that the relationship between anesthetic agents and non-small cell lung cancer (NSCLC) prognosis remains controversial. Therefore, this retrospective cohort study was designed to investigate the effects of propofol or sevoflurane anesthesia on the long-term oncologic outcomes of NSCLC patients. Methods: We identified 1,778 eligible patients (propofol-based total intravenous anesthesia (TIVA) group, n = 686, sevoflurane-based inhalation anesthesia (INHA) group, n = 1,092) out of 2,388 patients undergoing elective NSCLC surgery from June 2013 to June 2016 in the Harbin Medical University Cancer Hospital. The primary endpoints were 5-year overall survival and recurrence-free survival. The secondary endpoints were independent risk factors of cancer recurrence or all-cause mortality. Data were analysed with the propensity score matching, Kaplan-Meier survival and Cox multivariate analyses as appropriate. Results: After propensity score matching, there were 672 patients in each group. The median follow-up period was 69 months (interquartile range: 68 - 70 months) for all patients. Five-year overall survival was 75.7% (95% confidence interval (CI) 72.4 - 79.1) in the TIVA group and 71.8% (68.4 - 75.4) in the INHA group (P = 0.160) (hazard ratio (HR), 0.86; 95%CI, 0.70 - 1.06; P = 0.158), and 5-year recurrence-free survival were 68.5% (65.0 - 72.2) and 62.7% (59.1 - 66.5 (P = 0.108) (HR, 0.90; 95%CI, 0.75 - 1.08; P = 0.253), respectively. Subgroup analyses showed there were no significant difference in overall survival or recurrence-free survival between two groups in each TNM stage of NSCLC. The independent risk factors included age ≥ 60 years old, male, blood transfusion, segmental/wedge resection and pneumonectomy, thoracotomy, postoperative complications, lung adenocarcinoma, TNM stages, high CEA and CYFRA211 levels, and postoperative radiotherapy. Conclusions: Our data indicated no difference between propofol-based TIVA and sevoflurane-based INHA in terms of 5-year overall survival and recurrence-free survival after NSCLC surgery.